Epistemologia Kanta jako rozwiązanie sporu empiryzmu z racjonalizmem - Wendland, Michał (Filozofia Publiczna i Edukacja Demokratyczna, 2012)
The article concerns some of the most important elements of I. Kant’s epistemology and its connections with earlier epistemological ideas, namely rationalism and empiricism. The history of dispute between rationalism (Descartes, Leibniz) and empiricism (Locke, Berkeley, Hume) is hereby shortly presented while Kant’s own philosophical achievements are suggested to be both alternative and synthesis of these. The main core of this paper is summary of basis of Kant’s Critique of Pure Reason; some most important categories are described: apriorism, synthetic and analytical judgements, knowledge a priori and a posteriori, main ideas of transcendental esthetics (two forms of pure intuition: time and space), main ideas of transcendental logic (forms of judgement and twelve categories). Also the meaning of Kant’s „copernican revolution” is presented as a turning point for classical German philosophy as well as for whole modern epistemology.